The Labor Market: An Overview from an Islamic Perspective - Hanifiyah Yuliatul Hijriah; Elfira Maya Adiba (TIJAB (The International Journal of Applied Business), 2019)
The concept of employment has some aspects that are integrated in order to achieve the balance of the workforce, both aspects of demand and supply of labor. The labor market is considered as the location of meeting between the demand for labor from both the private and Government sectors and the supply of labor available. The meeting of demand and supply of manpower can exert influence on the determination of the level of wage labor. In other words, the labor market plays a role in assisting the Government in the process of making employment-related policies such as the determination of the level of wages. This study, by employing library research, demonstrated that the concept of labor as seen from the viewpoint of Islam will be able to reach the concept of labor. It is not limited to the extent of absorption of labor, but also related how the level of the workforce that is capable of being managed by the Government to be more productive. The policy of wage rate in Islam is not limited to referring to balance demand and supply of labor. It also reviews the needs of a worker based on the principle of fairness and honesty, and protects both interests in the worker and the employer. The essence of Islamic economy in review market power based on the view of Islam shows its potential in generating equitable economy society and realize prosperity.